Blood Conservation and Hemostasis in Cardiac Surgery: A Survey of Practice Variation and Adoption of Evidence-Based Guidelines. (July 2021) - Joshi, Ravi V.; Wilkey, Andrew L.; Blackwell, James-Michael; Kwak, Jenny; Raphael, Jacob; Shore-Lesserson, Linda; Greilich, Philip E.
Abstract : BACKGROUND: Blood conservation and hemostasis are integral parts of reducing avoidable blood transfusions and the associated morbidity and mortality. Despite the publication of blood conservation guidelines for cardiac surgery, evidence suggests persistent variability in practice patterns. Members of the Society of Cardiovascular Anesthesiologists (SCA) created a survey to audit conformance to existing guidelines and use the results to help narrow the evidence-to-practice gap. METHODS: Members of the SCA and its Continuous Practice Improvement (CPI)— Blood Conservation Work Group developed a 48-item Blood Conservation and Hemostasis in Cardiac Surgery (BCHCS) survey. The questionnaire included the components of the Anesthesia Quality Institute's (AQI) composite measure AQI49. The survey was distributed to the entire SCA membership by e-mail via the Research Electronic Data Capture (REDCap) Consortium between the fall of 2017 and early 2018. RESULTS: Of 3152 SCA members, 536 returned surveys for a response rate of 17%. Most responders worked at academic institutions. The median transfusion trigger after cardiopulmonary bypass was hemoglobin (Hgb) 7.0 to 8.0 g/dL. There are 4 components to AQI49, and the composite conformance to all of them was low due to 1 specific component: the use of transfusion algorithms supplemented with point-of-care (POC) testing. There was good conformance to the other 3 components of AQI49: use of antifibrinolytics, minimization of hemodilution and use of red cell salvage. Overall, practices with a multidisciplinary patient blood management (PBM) team were the most successful in meeting all 4 AQI49 criteria. CONCLUSIONS: The survey demonstrated widespread adoption of several best practices, including the tolerance of lower hemoglobin transfusion triggers, use of antifibrinolytics, minimization of hemodilution, and use of red cell salvage. The survey also confirms that gaps remain in preoperative anemia management and the use of transfusion algorithms supplemented with POC hemostasis testing. Serial use of this survey can be used to identify barriers to implementation and audit the effectiveness of interventions described in this article. This instrument could also help harmonize local, regional, and national efforts and become an essential component of an implementation strategy for PBM in cardiac surgery.